Non-Invasive Cardiac Output Measurement in Low and Very Low Birth Weight Infants: A Method Comparison - Grollmuss, Oswin; Gonzalez, Patricia (Frontiers in Pediatrics, 2014)
Background : Cardiac output (CO) measurement in low (LBW) and very low (VLBW) birth weight infants is difficult. Hitherto, sporadical transthoracic echocardiography (TTE) is the only non-invasive measurement method. Electrical velocimetry (EV) has been evaluated as an alternative in normal weight newborns. Objectives: The study was designed to evaluate if EV could even be interchangeable with TTE in LBW and VLBW infants. Methods: In 28 (17 LBW, 11 VLBW) premature newborns, n = 228 simultaneous TTE (transaortic Doppler) and EV measurements (134 LBW, 94 VLBW) of stroke volume (SV) and heart rate (HR) were performed, thereof calculating body weight indexed SV (= SV*) and CO (= CO*) for all patients and the subgroups. Method comparison was performed by Bland-Altman plot, method precision expressed by calculation of the coefficient of variation (CV). Results: Mean CO* in all patients was 256.4 ± 44.8 (TTE) and 265.3 ± 48.8 (EV) ml/kg/min. Bias and precision were clinically acceptable, limits of agreement within the 30% criterion for method interchangeability (Critchley and Critchley, 1999). According to their different anatomic dimensions and pathophysiology, there were significant differences of SV(*), HR and CO* for LBW and VLBW infants as well for inotropic treatment and ventilation mode. Conclusions: Extending recent publications on EV/TTE comparison in newborns, this study suggests that EV is also applicable in LWB/VLBW infants as a safe and easy to handle method for continuous CO monitoring in the NICU and PCICU.